CONDENSING LENS ON BINOCULAR INDIRECT OPHTHALMOSCOPY AND SLIT-LAMP BIOMICROSCOPY - Danang Yoga Wiguna; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (International Journal of Retina, 2019)
Condensing lens is a lens used as an auxiliary lens in indirect instruments to examines the fundus. This lens is used with binocular indirect ophthalmoscope and slit-lamp biomicroscope to reach a stereopsis image of fundus. Optical principle of condensing lens is to make the eye in myopic condition, so it can producesa real, aerial, inverted and reversed image. This lens was placed between the instruments and the eye of the patient which located closer to patient’s eye. Optimalized position of the lens can produce a good fundus image. Condensing lens have so many power of dioptre that each power produces different magnification and field of view. High powered lenses produces wider field of view than low powered ones. High powered lens can also used in patient with small dilated pupil and shorter distance of examination. Low powered lenses offer more magnification. Fundus examination with binocular indirect ophthalmoscope and slit-lamp biomicroscope have purpose to produces stereopsis image because of the binocularity system. These two instruments have each advantages and disadvantages. The advantages of binocular indirect ophthalmoscope are a portable instrument, relatively can be used in uncooperative patient and it can be used with scleral indentation to reach more peripheral view of the fundus. Meanwhile slit-lamp biomicroscope has the advantages to offer more magnification and flexible illumination system. With higher powered lens use in biomicroscope, it also give advantages in shorter distance of examination and wider field of view.